The Island Literature Museum in Korea - Shin, Inseop (Archīum Ateneo, 2024)
The literature museum serves as a unique locale that emits the symbolism and cultural essence of literature, enhancing the image of a region. However, in Korea, islands have long been estranged from literature due to insufficient literary infrastructure. Conversely, from a mainland-centric perspective, islands have often been considered as peripheral cultural spaces for poetry and novels. This study focuses on the regional characteristics of islands in Korea and examines the relationship between literature and islands through case studies of Jeju Island’s Literature Museum, Yun Seon-do Literature Museum of Bogildo, and Literary Island Nodo. Each of these island literature museums presents unique approaches in either reclaiming their marginalized identities or highlighting their historical literary significance in contrast to the mainland. For instance, Jeju Island’s Literature Museum seeks to restore its identity in the spirit of resisting against homogenizing discourses of the mainland. On the other hand, islands like Bogildo and Nodo emphasize the importance of literature due to their historical experiences of exile, leading them to establish new literary infrastructures to foster literary expressions and to effectively disseminate their own narratives. Furthermore, island literature museums serve as catalysts for generating new forms of storytelling that emerge from the narratives they present. The storytelling that arises from these island literature museums, facilitated by the movement of people and information, reflects the evolving significance of islands interwoven with literature.